2008
DOI: 10.1097/brs.0b013e3181657d93
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Neurological Deficits of Surgical Correction for Scoliosis

Abstract: In surgical correction of scoliosis, the risk factors for neurologic deficits include CS, scoliosis with hyperkyphosis, scoliosis correction by combined procedures, scoliosis with a Cobb's angle more than 90 degrees , and a revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 22 publications
1
56
0
Order By: Relevance
“…New neurological deficits were seen with revision procedures. Qiu et al [13] found that the use of combined procedures, Cobb angle [90°, hyperkyphosis and revision surgery were risk factors for neurological deficits.…”
Section: Neurological Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…New neurological deficits were seen with revision procedures. Qiu et al [13] found that the use of combined procedures, Cobb angle [90°, hyperkyphosis and revision surgery were risk factors for neurological deficits.…”
Section: Neurological Complicationsmentioning
confidence: 99%
“…Recently, large database studies on complications of scoliosis surgery have been published [7,9,13,14]. Although these studies benefit from large patient populations, they might be prone to underreporting.…”
Section: Introductionmentioning
confidence: 99%
“…Possible factors associated with higher risk of neurological complications of scoliosis surgery are represented by congenital scoliosis, scoliosis combined with hyperkyphosis, severity of the curve (Cobb angle over 90°), combined approach surgery, revision surgery and decreased spinal cord perfusion due to hypotension and/or significant haemorrhage. Procedures associated with higher risk include vertebral osteotomies and kyphosis correction [1,2]. There exists an urgent need for a method to warn the spine surgeon of impending neurological deficits during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…3 Factors such as scoliosis with the major curve greater than 90°, hyperkyphosis, congenital scoliosis, combined anterior and posterior surgeries, and multiple surgeries are shown to increase the incidence of neurological events. 2,3,6,13 To prevent these complications, different neuromonitoring modalities have been used during the last 4 decades including monitoring of SSEPs, motor evoked potentials (MEPs), and the wakeup test. Despite the historical success of SSEP and earlier satisfactory results in intraoperative assessment of neurological function, 4,10 its capability to detect the descending motor tract was soon questioned.…”
Section: Discussionmentioning
confidence: 99%